2015
DOI: 10.1111/jne.12323
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Stage and Modulation of Stress‐Induced Tau Phosphorylation in Female Rats

Abstract: Chronic stress is implicated as a risk factor for Alzheimer's disease (AD) and other neurodegenerative disorders. While the specific mechanisms linking stress exposure and AD vulnerability have yet to be fully elucidated, our lab and others have shown that acute and repeated restraint stress in rodents leads to an increase in hippocampal tau phosphorylation (tau-P) and tau insolubility, a critical component of tau pathology in AD. Tau phosphorylation induced by a psychological stressor is reversible and is tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…We found that exposure to one episode of restraint stress significantly reduced p-Tau in the hippocampus of lactating dams compared to virgin or postweaned rats. This decrease was coupled with reduced detection of GSK3α ( 23 ).…”
Section: Hormone Actions and Their Relation To Neurodegenerative Disementioning
confidence: 99%
See 3 more Smart Citations
“…We found that exposure to one episode of restraint stress significantly reduced p-Tau in the hippocampus of lactating dams compared to virgin or postweaned rats. This decrease was coupled with reduced detection of GSK3α ( 23 ).…”
Section: Hormone Actions and Their Relation To Neurodegenerative Disementioning
confidence: 99%
“…The fact that diverse results in the AD field have surfaced between males and females at different ages, reproductive stages, and in response to different stimuli points toward a new direction in sex-related AD research ( 23 , 45 , 77 ) (Table 1 ). Thus, detailed attention must be given to the study of aging, different reproductive stages and hormones involved, and the interplay with other risk factors in females ( 21 , 77 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, PRL may regulate neurogenesis, contribute to stress adaptation, and promote neuroprotection; however, PRL also inhibits neurogenesis and promotes depressive-like behaviors [5]. Furthermore, a previous study reported PRL caused negative effects on cognitive function in patients with AD, but another study showed that PRL reduced the risk of AD via inhibition of tau phosphorylation and protected the hippocampus [12, 13]. In a case-control study, PRL responses to fenfluramine were significantly impaired in patients with PD compared to controls and were significantly more blunted in patients with major depression compared to the nondepressed group [14].…”
Section: Introductionmentioning
confidence: 99%